Relationship Between the Salivary Microbiome and Oral Malodor Metabolites in Older Thai Individuals with Periodontitis and the Cytotoxic Effects of Malodor Compounds on Human Oral Squamous Carcinoma (HSC-4) Cells - Witsanu Srila; Kritsana Sripilai; Thunwa Binlateh; Peungchaleoy Thammanichanon; Watcharaphol Tiskratok; Parinya Noisa; Paiboon Jitprasertwong (Dentistry Journal)
Background/Objectives: Halitosis is primarily caused by the activity of oral microorganisms. In this study, we employed metagenomic sequencing and metabolomic approaches to investigate the differences in salivary microbiota and metabolite profiles between individuals with halitosis and periodontitis and healthy controls. Additionally, we expanded the study to examine how oral malodorous compounds interact with human oral squamous carcinoma (HSC-4) cells. Methods: Saliva samples were collected and analyzed using Ultra-High Performance Liquid Chromatography–Mass Spectrometry (UHPLC-MS) to identify metabolites. We then assessed the correlations between the microbiota and metabolites. Furthermore, the impact of oral malodorous substances on HSC-4 cells was investigated by evaluating apoptosis, antioxidant activity, and inflammatory properties. Results: The microbiota and metabolite profiles showed significant differences between the halitosis with periodontitis group and the periodontally healthy group. The halitosis with periodontitis group exhibited significantly higher relative abundances of eight genera: Tannerella, Selenomonas, Bacteroides, Filifactor, Phocaeicola, Fretibacterium, Eubacterium saphenum, and Desulfobulbus. In contrast, the periodontally healthy group showed significantly higher relative abundances of Family XIII UCG-001, Haemophilus, and Streptobacillus. Two metabolites, 2,3-dihydro-1H-indole and 10,11-dihydro-12R-hydroxy-leukotriene E4, were significantly higher in individuals with halitosis and periodontitis. In the treatment of HSC-4 cells with metabolites, dimethyl sulfide (DMS) did not show significant effects while indole appeared to induce cell death in HSC-4 cells by triggering apoptotic pathways. Additionally, both indole and DMS affected the inflammatory and antioxidant properties of HSC-4 cells. Conclusions: This study provides insights into the mechanisms of halitosis by exploring the correlations between microbiota and metabolite profiles. Furthermore, oral metabolites were shown to impact the cellular response of HSC-4 cells.